Characterization of a Mechanically Tunable Gyroid Photonic Crystal Inspired by the Butterfly Parides Sesostris. Issue 1 (25th September 2015) - Pouya, Caroline; Overvelde, Johannes T. B.; Kolle, Mathias; Aizenberg, Joanna; Bertoldi, Katia; Weaver, James C.; Vukusic, Pete
Abstract : A mechanically tunable macroscale replica of the gyroid photonic crystal found in the Parides sesostris butterfly's wing scales is systematically characterized. By monitoring both photonic frequency changes and the distribution of stress fields within the compressed structure, electromagnetic transmission features are found and can be frequency‐tuned and the structure only contains localized high stress fields when highly compressed.